The Human Body and the Plant World: Mutual Relations of the Codes - Kolosova, Valeria B. (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2021)
The article analyses reflections of the anthropomorphic code in the plant code of traditional Slavonic culture. There exist: 1) the language level (using body parts names in phytonyms); 2) the folklore level (aetiological stories about the genesis of plants from the human body); and 3) the level of ritual (using body parts to influence the plants, rules and taboos concerning planting). Plants are also used to influence the human body (usually in folk medicine) on the basis of similarity of their parts.